The Cipp Model-Based Evaluation on Integrated English Learning (IEL) Program at Language Center - Agustina, Noor Qomaria; Mukhtaruddin, Fanni (English Language Teaching Educational Journal, 2019)
The competition in the workforce demands quality programs to make the learners to have competitive advantage by mastering the foreign language especially English. Language Training Centre is one institution that provide service on teaching language skill. The aim of this research was to make an evaluation on the program conducted by the Centre using the CIPP Model developed by Stufflebeam that evaluated the effectiveness and quality of the program seen from the context, input, process and product, and was applied for a program namely Integrated English Learning (IEL). The methodology was the combination of quantitative and qualitative design. The setting was a a language Center and the participants were the students from two departments. This study described the program from the point of view of its context, input, process and product. The context is seen from the effectivity of the program, while the input discusses about the quality.  The process is to describe the implementation of the program and the product reveals how the goals are achieved.